Effect of Needle Size and Needle Height to Substrate in Encapsulation Process of LED Packaging - Alim M.A.; Abdullah M.Z.; Aziz M.S.A.; Kamarudin R.; Rusdi M.S.; Ishak M.H.H.; Gunnasegaran P. (Springer Science and Business Media Deutschland GmbH, 2023)
The purpose of this study is to investigate the effect of needle size and substrate to needle height by measuring the droplet volume and epoxy covered area in encapsulation process of LED packaging. Five needle gages (16G, 18G, 21G, 22G, and 23G) were used in this experiment. Average volume of epoxy drops was determined for each size of needle. Experimental data shows that droplet volumes are directly related with the needle diameter. Optimum covered area by the epoxy encapsulation was found at the needle tip to substrate distance at 3.240mm for the 16G needle. These findings are relevant and helpful for controlling the amount of epoxy, encapsulation area, and the encapsulant shape in encapsulation process of LED packaging. 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.